Aportació al coneixement dels macromicets de l'illa de Mallorca II - Pérez-De-Gregorio i Capella, Miquel Àngel (Revista Catalana de Micologia, 2007)
A contribution to the knowledge of the macromycetes of Majorca Island. II.(Balearic Islands). This work reports 40 species: 3 Ascomycetes and 37 Basidiomycetes. Afterour information, 37 of them are new records for the Balearic Islands, and a further 3 are newrecords for Majorca. Of special interest are: Suillus bellinii f. lutea forma nova, Boletus dryophilus, Greletia ovalispora, Peziza saccardiana, Trametes hirsuta, Clitocybe cistophila,Cortinarius sodagnitus, Cortinarius subfulgens, Hebeloma pyrophilum, Hygrophorusquercetorum, Marasmius carphaticus, Mycena polyadelpha and Hydnangium aurantiacum.